2000
DOI: 10.1021/la9912388
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Free Osmium Clusters Supported on MgO. A Density Functional Study

Abstract: The interactions of Os4, Os5, and Os5C clusters with various sites of a MgO(001) support were investigated theoretically with the aid of a scalar-relativistic density functional cluster model method. Adsorption geometries of C4v clusters centered above a magnesium cation and the Os atoms oriented either to the nearest surface oxygen anions (A) or between them (B) were considered. The influence of surface Vs and Vs 2-defects on the adsorption of the clusters was also investigated. The calculated base Os-Os dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
51
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 45 publications
11
51
1
Order By: Relevance
“…DFT calculations [14] show that metal clusters are bonded to MgO by metal-oxygen bonds, [15] consistent with the results observed generally by EXAFS spectroscopy for Group 8 metal clusters on metal oxides [16] and in agreement with our EXAFS results as well. (EXAFS data indicate distortion of CO ligands on adsorbed metal clusters to accommodate to the support surface.)…”
supporting
confidence: 91%
See 1 more Smart Citation
“…DFT calculations [14] show that metal clusters are bonded to MgO by metal-oxygen bonds, [15] consistent with the results observed generally by EXAFS spectroscopy for Group 8 metal clusters on metal oxides [16] and in agreement with our EXAFS results as well. (EXAFS data indicate distortion of CO ligands on adsorbed metal clusters to accommodate to the support surface.)…”
supporting
confidence: 91%
“…The images of the clusters shown in Figure 2 provide a basis for determining a model of the structures of the clusters that include the Osoxygen bonds indicated by the EXAFS data [16] and DFT calculations. [15] We investigated all the models of the structures of the clusters on the MgO(110) face that match the data-that is, those having 3 Os atoms atop Mg atoms arranged in a triangle that is isosceles when viewed from the top and anchored through OsÀO bonds. The models are based on the observed OsÀOs distances and the structures of sites known to exist on MgO(110).…”
mentioning
confidence: 99%
“…These distances are markedly greater (by about 0.2-0.3 Å) than the metal-metal distances in the free (gas-phase) clusters (e.g., Ir 4 , 2.44 Å) [51]. Similar results have been determined for supported Os 5 C [52] and Rh 6 [53]. These comparisons led the Rösch group [51,52] to conclude that some ligands remain on the clusters after decarbonylation; this conclusion may be quite general.…”
Section: Structural Characterizationsupporting
confidence: 77%
“…Similar results have been determined for supported Os 5 C [52] and Rh 6 [53]. These comparisons led the Rösch group [51,52] to conclude that some ligands remain on the clusters after decarbonylation; this conclusion may be quite general. The candidate ligands include C (from CO ligands of the precursor) and H (from the support).…”
Section: Structural Characterizationsupporting
confidence: 72%
“…The MgO(100) surface in general is highly studied as a supporting material for metal clusters. 28,29 Hence, motivation exists to investigate a model system of sub-nanometer Pt and Pt-Zn clusters deposited on MgO(100) surfaces. It is noted that, previously, others have shown that nanometer sized clusters of group 10 elements (in particular, clusters of Pt, Pd, and Pt-based bi-metallics) undergo morphological changes when deposited on oxide supports, including MgO.…”
Section: Introductionmentioning
confidence: 99%